2006
DOI: 10.1002/pmic.200600208
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric genomic data mining: Novel insights into bioenergetic pathways inChlamydomonas reinhardtii

Abstract: A new high-throughput computational strategy was established that improves genomic data mining from MS experiments. The MS/MS data were analyzed by the SEQUEST search algorithm and a combination of de novo amino acid sequencing in conjunction with an error-tolerant database search tool, operating on a 256 processor computer cluster. The error-tolerant search tool, previously established as GenomicPeptideFinder (GPF), enables detection of intron-split and/or alternatively spliced peptides from MS/MS data when d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 74 publications
2
51
0
2
Order By: Relevance
“…Proteomic studies indicated that TEF22 is in the mitochondrion (Allmer et al, 2006;Atteia et al, 2009), whereas localization prediction programs (WolfPsort) place Cre14.g609900 and Cre13. g586600 at the plasma membrane.…”
Section: Iron Assimilation: Transporters and Ferrireductasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic studies indicated that TEF22 is in the mitochondrion (Allmer et al, 2006;Atteia et al, 2009), whereas localization prediction programs (WolfPsort) place Cre14.g609900 and Cre13. g586600 at the plasma membrane.…”
Section: Iron Assimilation: Transporters and Ferrireductasesmentioning
confidence: 99%
“…TEF22 is induced 7.6-and 17-fold in photoheterotrophic cells in response to iron deficiency and iron limitation, respectively, and in CO 2 -grown cells even more dramatically, although the expression is always higher in acetate-grown cells. TEF22, located in the mitochondrion based on two proteomic studies (Allmer et al, 2006;Atteia et al, 2009), has a cytochrome b 561 ferric-reductase domain at its C-terminal end (see Supplemental Figure 4 online). It is distinct from the classical cytochrome b 561 -only containing proteins as TEF22 also contains a soluble heme binding DOMON domain in the central region.…”
Section: Iron Assimilation Components Transporters and Ferric-chelamentioning
confidence: 99%
“…Only two isoforms have been identified in C. reinhardtii thylakoid membranes: FtsH1 (type A) and FtsH2 (type B; Allmer et al, 2006). Our two-dimensional BN/SDS-PAGE and coimmunoprecipitation experiments demonstrate that FtsH1 also forms heterocomplexes with FtsH2 in C. reinhardtii ( Figures 3D and 3E).…”
Section: Discussion the Thylakoid Ftsh Protease Of C Reinhardtii Formentioning
confidence: 73%
“…Thylakoid FtsH proteases form various heterohexamers in cyanobacteria (Boehm et al, 2012) and Arabidopsis (Sakamoto et al, 2003;Yu et al, 2004;Zaltsman et al, 2005;Moldavski et al, 2012). Whereas four isoforms of thylakoid FtsH were identified in Arabidopsis (Zaltsman et al, 2005), only two thylakoid isoforms, FtsH1 and FtsH2, have been identified by proteomic studies in C. reinhardtii (Allmer et al, 2006). We raised specific antibodies against peptides from each of these isoforms (see Methods).…”
Section: Map-based Cloning Of the Point Mutation Ftsh1-1mentioning
confidence: 99%
“…In Chlamydomonas, an ortholog of CAS (Cre12.g497300) was also detected in the thylakoid membrane fraction (23,24). It was proposed that CAS is required for photoacclimation by regulating induction of lightharvesting complex stress-related protein 3 (LHCSR3) (25) and for forming a super complex for photosynthetic cyclic electron flow (CEF) in anaerobic conditions (26).…”
Section: +mentioning
confidence: 99%